2009
DOI: 10.4103/0189-6725.48571
|View full text |Cite
|
Sign up to set email alerts
|

Childhood burns in south eastern Nigeria

Abstract: Burns is still a major health problem among children in south eastern Nigeria. Fortunately, outcome of appropriate treatment is good. However, we think that poor safety consciousness among parents is a major predisposing factor. Public enlightenment on measures to ensure safe home environment may be necessary to avoid or limit childhood burns.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

11
28
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(39 citation statements)
references
References 5 publications
11
28
0
Order By: Relevance
“…In agreement with other studies [5-7,16,17], the majority of patients in this study were aged 2 years and below. High incidence of burn injuries in children reflects lack of coordination and unawareness of dangerous substances in this age group.…”
Section: Discussionsupporting
confidence: 94%
See 2 more Smart Citations
“…In agreement with other studies [5-7,16,17], the majority of patients in this study were aged 2 years and below. High incidence of burn injuries in children reflects lack of coordination and unawareness of dangerous substances in this age group.…”
Section: Discussionsupporting
confidence: 94%
“…In our study, males were slightly more affected than females with a male to female ratio of 1.4:1 which is in agreement with other studies [6,7,18]. The reasons for the male preponderance in our study may be attributed to the overactive nature of male babies as compared to the females.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…[14] In the current study hot water was responsible for most of the burns injury as widely reported in other studies. [13][14][15][16] Regarding the anatomic region of injury, extremities were the most commonly injured parts followed by head region [ Table 2]. This is similar to report by Karbakhsh et al, [8] Adesunkanmi et al .…”
Section: Discussionsupporting
confidence: 88%
“…; (Ekenze et al, 2009;Ifesanya et al, 2009;Melliez et al, 2007;Okafor et al, 2009;Okoro et al, 2009). Many other studies that are not hospital-based, but population-based failed to consider the influence of contextual situation where children are raised on their survival chances.…”
Section: Introductionmentioning
confidence: 99%